Theoretical Study on the Mechanism of the CH₃OH + ·XH₃ (X = C, Si) Reactions - Nguyen, Trong Nghia; Nguyen, Ngoc Tue (Old Journal, 2019)
The mechanism for the reactions of methanol (CH₃OH) with ·XH₃ (X = C, Si) radicals have been investigated by ab initio molecular orbital theory based on the CCSD(T)//B3LYP/aug-cc-pVTZ method. For the CH₃OH + ·CH₃ reaction, the major product pathways channels are H-abstraction forming PR1 (·CH₂OH + ·CH₄; 0 kcal·mol⁻¹) and PR2 (·CH₂OH + CH₄; -8.1 kcal·mol⁻¹) via transition states TS1 and TS2 lying 12.0 and 12.8 kcal·mol⁻¹ above the reactants, respectively. While for the CH₃OH + ·SiH₃ reaction, the major product pathways channels are the H-abstraction forming PR7 (·CH₂OH + SiH₄; 3.4 kcal·mol⁻¹) and substitution channels forming PR8 (H + CH₃OSiH₃; -0.3 kcal·mol⁻¹) and PR9 (·CH₃ + SiH₃OH; -28.7 kcal·mol⁻¹) via transition states TS7 (16.2 kcal·mol⁻¹), TS8 (16.5 kcal·mol⁻¹) and TS9 (17.0 kcal·mol⁻¹), respectively. The predicted geometry parameters for the species in the PESs and the heats of reaction in this work are in good agreement with available experimental data.